TINDAK TUTUR NGGAHI PANATI DALAM PROSESI LAMARAN PERNIKAHAN ADAT BIMA: SUATU KAJIAN PRAGMATIK SERTA IMPLIKASINYA DALAM PEMBELAJARAN MULOK DI SEKOLAH - irham irham (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2017)
Abstract There are three aspects of the meaningfulness of speech acts Nggahi Panati in procession Bima customary marriage proposal, namely the form of speech acts, cooperation aspects, and aspects of politeness. This study aims to determine the significance of the speech act in a procession Nggahi Panati Bima customary marriage proposal and its implications for the learning of local content in local language school. The results showed that the form of speech act category Nggahi Panati representative (states, states, and reporting), categorized directive (beg, ask, and urge), expressive category (praise, laud, and grateful), category commissive (promise and declare readiness ), and categorized declarative (grant and decide). The study concluded also that aspects of cooperation and aspects of speech acts Nggahi Panati in politeness very considered and prioritized by the speaker and hearer in speaking. In addition to the use of idioms, speaker and hearer using rhymes and language metaphor anyway.